Aspect-based Sentiment Analysis based on Graph Convolutional Network - He, Bo; Zhang, Hongqian; Han, Hao; Chen, Yunfei (International Journal of Computer Science and Information Technology, 2025)
Aspect-based sentiment analysis (ABSA), a critical task in the field of natural language processing, aims to identify and analyze the sentiment orientation towards specific aspects within texts. In recent years, Graph Convolutional Networks (GCN), as a potent type of graph neural network, have demonstrated unique advantages in handling graph-structured data, offering new perspectives and methods for ABSA. In this paper, we provide an overview of the research progress in graph convolution-based ABSA methods. Initially, it introduces three pivotal methods in the ABSA domain, encompassing representative work based on dictionaries, machine learning, and deep learning, while analyzing their strengths and limitations. Subsequently, it elaborates on graph convolution-based ABSA methods, highlighting existing problems and challenges in current research. Finally, we further explore future research directions for ABSA, particularly in achieving more accurate analyses of nuanced emotional expressions within textual content.